Effect of a compatibilizing agent on yttrium-doped BaTiO3 particles in the dielectric behavior of silicone rubber composites (Superficies y Vacío, 2012)
This paper studies the compatibilizing effect of four different carboxylic acids in the dielectric behavior of polymer/ceramic composites. Pure and yttrium doped BaTiO3 powder is used as filler of RTV silicone rubber composites. It was found that stearic acid efficiently functionalized the ceramic surface maintaining in good level its dielectric constant and lowering its dielectric loss and electrical conductivity. The composites made with this filler also have improved dielectric properties which are desirable due to electrical insulation applications that will give the composite. Finally, simulations of the electric field in a transformer bushing whose coating is made of these composites were made. It was found that the joint action of the improved permittivity of the composites produced, the functionalization of the filler and even a slight redesign of the insulator in conflict zones could achieve much better performance for longer.